ROOTS CHARACTERISTICS AND EFFECTS OF CONTAINERS ON THE QUALITY OF TOONA CILIATA M. ROEMER SEEDLINGS - Matos, Priscila Silva; Oliveira, Jessica Costa de; Medeiros, Walleska Pereira; Novaes, Adalberto Brito de (Floresta, 2022)
The objective was to evaluate the effects of recipients and root characteristics on the quality of Australian cedar seedlings. The research was carried out in two stages, the first consisted of seedling production in the nursery and evaluation of morphological parameters, and the second consisted of evaluating the potential for root regeneration. There were five treatments involving two production systems for seedlings, tubes, and plastic bags: T1 – tube (288 cm3); T2 – tube (120 cm3); T3 - tube (55 cm3); T4 - plastic bags (424 cm3); and T5 - plastic bags (216 cm3). The seeds used are from a matrix tree located at the State University of Southwest Bahia. The design of the experiment was a completely randomized design with four replications. The morphological parameters evaluated were a) shoot height (H); b) neck diameter (D); c) fresh and dry biomass of shoots and roots; d) H/D, H/SDM, and shoot and root dry mass ratio (SDM/RDM); e) Dickson Quality Index (DQI), and f) the total number of regenerated roots present in the upper and lower parts of each container. The results showed that the tubes with 288 cm³ of volumetric capacity produced seedlings with higher averages for the morphological and root characteristics, constituting the ideal production system for Australian cedar seedlings. In the absence of tubes with 288 cm³, it is possible to use plastic bags (424 cm³) for this species. The evaluated root regeneration potential proves to be a favorable prognosis of rapid establishment and performance of seedlings in the field.